Mucor circinelloides: Growth, Maintenance, and Genetic Manipulation. Issue 1 (27th April 2018) - Vellanki, Sandeep; Navarro‐Mendoza, Maria Isabel; Garcia, Alexis; Murcia, Laura; Perez‐Arques, Carlos; Garre, Victoriano; Nicolas, Francisco E.; Lee, Soo Chan
Abstract: Mucor circinelloides is a fungus that belongs to the order Mucorales. It grows as mold in the environment and can cause mucormycosis, a potentially fatal infection in immunocompromised patients. M. circinelloides is a biodiesel producer and serves as a model organism for studying several biological processes, such as light responses and RNA interference–mediated gene silencing. Over the past decade, the increasing number of molecular tools has also allowed us to manipulate the genome of this fungus. This article outlines the fundamental protocols for the in vitro growth, maintenance, and genetic manipulation of M. circinelloides in the laboratory. © 2018 by John Wiley & Sons, Inc.